2001
DOI: 10.1054/bjoc.2001.1997
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis is an independent prognostic factor in malignant mesothelioma

Abstract: Summary Angiogenesis is essential for tumour growth beyond 1 to 2 mm in diameter. The clinical relevance of angiogenesis, as assessed by microvessel density (MVD), is unclear in malignant mesothelioma (MM). Immunohistochemistry was performed on 104 archival, paraffinembedded, surgically resected MM samples with an anti-CD34 monoclonal antibody, using the Streptavidin-biotin complex immunoperoxidase technique. 93 cases were suitable for microvessel quantification. MVD was obtained from 3 intratumoural hotspots,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 53 publications
6
75
0
1
Order By: Relevance
“…35,39,42,65 In our study, we also showed that survival time and relapse time were significantly shorter in NSCLC patients with tumors with high total COX-2 mRNA expression in cancer cells and stromal cells. Several studies have investigated the prognostic significance of COX-2 expression in NSCLC but with different results.…”
Section: Discussionsupporting
confidence: 65%
“…35,39,42,65 In our study, we also showed that survival time and relapse time were significantly shorter in NSCLC patients with tumors with high total COX-2 mRNA expression in cancer cells and stromal cells. Several studies have investigated the prognostic significance of COX-2 expression in NSCLC but with different results.…”
Section: Discussionsupporting
confidence: 65%
“…High MVD is associated with a poor outcome in this disease (Kumar-Singh et al, 1997;Edwards et al, 2001), in keeping with the results from similar studies in other solid tumours (Dickinson et al, 1994;Fox et al, 1994;Cox et al, 2000c). Furthermore, in other solid tumours, such as nonsmall cell lung cancer, novel biological staging systems are being developed, which contribute independently to TNM stage (Cox et al, 2000a;O'Byrne et al, 2001).…”
supporting
confidence: 74%
“…As expected, prolonged inflammation causes the level of COX-2 to increase, which is actually recognized as an important malignant mesothelioma prognostic factor (30,31). A recent study has clearly shown that COX-2 expression is a strong prognostic factor in human mesothelioma, which contributes independently to other clinical and histopathologic factors in determining short survival (31).Although the regulation of mRNA stability seems to be the most important regulatory step for COX-2 expression, several studies have reported that other mechanisms, such as transcriptional control or hypermethylation (32), are also involved in regulating COX-2 expression.…”
Section: Cyclooxygenasessupporting
confidence: 63%